Cyclic lagoonal sedimentation of the Oxfordian/Kimmeridgian within the Sierra del Madero. Northwestern Iberian Range. Soria province. - Wilde, S.; Mensink, H.; Mertmann, D. (Cuadernos de Geología Ibérica, 1990)
Sin resumen